Non-tuberculous mycobacterial pulmonary disease (NTM-PD) - van Ingen, Jakko (Henry Stewart Talks, 2015)
Milestones in Non-Tuberculous Mycobacteria research, 4 distinct disease entities of NTM, Fibro-cavitary NTM-PD, Nodular-Bronchiectatic NTM-PD, NTM hypersensitivity pneumonitis, Cystic Fibrosis and NTM, American Thoracic Society diagnostic criteria for NTM-PD, Clinical relevance differs by species, Currently recommended treatment regimens, Treatment outcomes